Awareness and use of ChatGPT and large language models: a prospective cross-sectional global survey in urology : education - Eppler, Michael; Ganjavi, Conner; Ramacciotti, Lorenzo Storino; Piazza, Pietro; Rodler, Severin; Checcucci, Enrico; Gomez Rivas, Juan; Kowalewski, Karl-Friedrich; Belenchón, Ines Rivero; Puliatti, Stefano; Taratkin, Mark; Veccia, Alessandro; et al. (European urology, 2024)
Background - Since its release in November 2022, ChatGPT has captivated society and shown potential for various aspects of health care. - Objective - To investigate potential use of ChatGPT, a large language model (LLM), in urology by gathering opinions from urologists worldwide. - Design, setting, and participants - An open web-based survey was distributed via social media and e-mail chains to urologists between April 20, 2023 and May 5, 2023. Participants were asked to answer questions related to their knowledge and experience with artificial intelligence, as well as their opinions of potential use of ChatGPT/LLMs in research and clinical practice. - Outcome measurements and statistical analysis - Data are reported as the mean and standard deviation for continuous variables, and the frequency and percentage for categorical variables. Charts and tables are used as appropriate, with descriptions of the chart types and the measures used. The data are reported in accordance with the Checklist for Reporting Results of Internet E-Surveys (CHERRIES). - Results and limitations - A total of 456 individuals completed the survey (64% completion rate). Nearly half (47.7%) reported that they use ChatGPT/LLMs in their academic practice, with fewer using the technology in clinical practice (19.8%). More than half (62.2%) believe there are potential ethical concerns when using ChatGPT for scientific or academic writing, and 53% reported that they have experienced limitations when using ChatGPT in academic practice. - Conclusions - Urologists recognise the potential of ChatGPT/LLMs in research but have concerns regarding ethics and patient acceptance. There is a desire for regulations and guidelines to ensure appropriate use. In addition, measures should be taken to establish rules and guidelines to maximise safety and efficiency when using this novel technology. - Patient summary - A survey asked 456 urologists from around the world about using an artificial intelligence tool called ChatGPT in their work. Almost half of them use ChatGPT for research, but not many use it for patients care. The resonders think ChatGPT could be helpful, but they worry about problems like ethics and want rules to make sure it's used safely.